Inculturative and content potential of studying festive culture in the context of training at the “Stage Art” specialty in the dimensions of civic-mindedness and patriotism - Ostrovskaya Marina (ХДАК, 2023)
Currently we can testify the total nature of the loss of cultural values that occurring in society, the replacement of genuine values with imaginary ones, which is not only a kind of indicator of ongoing changes, but also a reflection of the need for innovative guidelines for society.
Keywords: stage art; theater education